Mutual partners' support in the process of the bereavement after the death of the child - Polona Ozbič (Psihološka Obzorja, 2015)
The death of a close person is one of the hardest situations which individuals face several times in their lifetimes. The death of a child is especially stressful. The partnership can be either mutually supportive or stressful; this is significantly related to coping with the loss. The purpose of the research was to study the mutual support of partners while grieving their child's loss. We conducted in-depth guided interviews with fourteen bereaved parents. We used a grounded theory to determine three main topics: the expectations of the bereaved from their partner; the characteristics of the mutual partners' support; and the relationship between partners in the process of bereavement. On the basis of these data the following categories prevailed: collective bereavement, individual bereavement with occasional collective bereavement, and isolated bereavement. Regardless of gender, the individuals with the first two patterns typically experience mutual understanding and the feeling of support in the process of bereavement. Those with the pattern of isolated bereavement have characteristically dysfunctional partnerships, which make mutual support difficult even when desired. Research showed a new finding in Slovenia: bereaved parents in functional partnerships often grieve individually and occasionally collectively, which they identify as adequate mutual support.